Design and implementation of double rotor switched reluctance motor using magnetic circuit analysis - Chockalingam Aravind Vaithilingam, (2013)
With its high robustness nature and simplicity in design, the switched reluctance machines are finding its way for most of the modern day applications. The torque generating capability of such machines highly depends on the energy density available in the air-gap. The energy density in the air-gap depends on the ux traverse as the rotor moves from its full non-overlap position to the overlap position towards the excited stator pole. One way to improve the air-gap energy density is through the reduction of the air-gap length and the other through the extension of ux-linking the stator and rotor pole surface (typically known as pole-arcs). The reduction of the air-gap length is limited to a minimal value due to the mechanical oscillations that develop as the machine picks up the speed. Also the pole-arc value has to be designed appropriately in order to avoid the uneven pull due to the sequential excitations of the phases. This eventually introduces high torque ripples and vibrations inside the machine. To address this issue a dual air-gap structure through a double rotor structure is proposed in this investigation. Initially the concept of the ux tube technique based on the integration techniques used in this analysis is introduced with respect to generic dual air-gap structure. In this method the energy density of a small strip in the uniform magnetic path of the structure is computed and then integrated over the whole surface, making the computation results more accurate. Unlike the conventional ux tube techniques where estimation of ux values are used in this analytical method the results are more accurate. The algorithm to derive the magnetic characteristics of the machine is presented. A quantitative analysis is performed on the various possible pole-arc values to derive the best possible com- binations to be used in the design of the double rotor structure. It is found from the analysis that with the outer rotor pole arc at 35', the inner rotor pole arc valve at 45', the stator inner surface pole arc at 30' and the outer surface pole arc at 50' the machine exhibit lesser Total Harmonic Distortion (THD)of 13.45%. Numerical evaluation of the results from the above analysis is performed using Finite Element Analysis (FEA) tool. The maximum torque in case of the numerical FEA is about 1.755 N-m whereas by the analytical method is about 1.652 N-m. The percentage error is due to the ux shape assumption in the analytical computations. The average torque for analytical is 0.947 N-m and through numerical is 0.953 N-m. The percentage error in the computation is about 6.35%. Analysis of the design of the dual rotor structure reveals particular aspects of dificulties to assemble. A support structure for both the stator and the rotor are developed. The fabricated machine is then tested to evaluate the analytical and the simulation results. In the full overlap La the error through FEA computations is about 12.90% due to the setting of the design parameter and about 8.13% error for the analytical due to practical limitation. In the full non-overlap condition Lu the error percentage is very small and is negligible. The time taken for the FEA simulation of one point is about 2 min 30 sec and the calculation of the iterations for one position is about 10 min. Numerical com- parative evaluations of the proposed machine with its conventional structure for the same volume and same mmf value is also performed through FEA. The maximum torque generated by the selected Double rotor switched reluctance machine is about 1.755 N-m with the THD value of 13.45%. The maximum torque generated by the conventional switched reluctance machine is about 1.272 N-m with THD value of 67.13%. This analysis is performed using the finite element tool. Motor Constant Square Density (G) is used as the comparative evaluation parameter and it is found that the proposed machine exhibit 65% increase in torque value compared to that of the conventional machine.